Publisher Correction: Combating subclonal evolution of resistant cancer phenotypes - Samuel W. Brady (Nature Portfolio, 2018)
The originally published version of this Article contained an error in Figure 4. In panel a, grey boxes surrounding the subclones associated with patients #2 and #4 obscured adjacent portions of the heatmap. This error has now been corrected in both the PDF and HTML versions of the Article.